The System Integrative Model of Psychotherapy and Counseling (SIMPC) to provide training focused on the professional development of psychologists and other specialists of the helping profession (Actual Problems of Psychology in Educational Institutions, 2019)
The article analyzes the features of a systematic approach tothe organization and structuring of the consultative and therapeutic process.The authors present the System Integrative Model of Psychotherapy andCounseling (SIMPC). The article details the features of each stage of workwithin the framework of the proposed model: precontact; first meeting;research; design and conceptualization; changes and development; stabilization;completion and postcontact.The authors offer a comprehensive multi-module author's program“System Integrative Counseling and Psychotherapy”, which is aimed at traininga system non-medical psychotherapist and consultant. It is designed forpsychologists and other s pecialists o f the helping professions. The programdetermines the content and structure of classes, has a practical orientation andcontributes to the formation of a professional holistic identity of a specialist.